Extensive Homologous Recombination among Widely Divergent TT Viruses - Worobey, Michael (American Society for Microbiology, 2000)
Analyses of a collection of full-length TT virus genomes showed nearly half of them to be recombinant. The results were highly significant and revealed homologous recombination both within and among genotypes, often involving extremely divergent lineages. Recombination breakpoints were significantly more common in the noncoding region of the TT virus genome than in the coding region.